Preparation process for evaporating cut-off film on surface of chalcogenide glass

By adopting a multi-layer evaporation cutoff film process on the surface of sulfur-based glass, the reflection problems caused by weakening information and high refractive index caused by the atmospheric environment of the infrared detector are solved, and the high-performance optical components of the infrared detection system are realized, which improves the Detect the spectral and mechanical properties of the device.

CN119307866APending Publication Date: 2025-01-14NANJING WAVELENGTH OPTO ELECTRONICS SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411304616.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Infrared detectors are weak in infrared information due to scattering or absorption losses in the atmospheric environment, and the high refractive index of components leads to reflection of contact interfaces, which reduces the quantum efficiency of the detection device and requires improving the overall performance of the detector.

Method used

The multi-layer evaporation cutoff film process is used on the surface of sulfur-based glass. Through the parameter setting of the coating machine and ion bombardment treatment, Ge, ZnS and YbF3 film layers are coated layer by layer to control the evaporation rate and physical thickness, and optimize the stress between films and layers. and adhesion, high-performance infrared detection system optical components are prepared.

Benefits of technology

The spectral performance and mechanical stability of the infrared detection system are achieved, the optical performance and reliability of the film layer are improved, and the transmittance and reflectivity performance of the detection device are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307866A_ABST
    Figure CN119307866A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process for evaporating a cut-off film on the surface of chalcogenide glass, and particularly relates to the technical field of infrared optical detection.The preparation process comprises the following steps that S01, the initial vacuum degree before execution of a coating machine is superior to 5.0 * 10 <-4 > Pa, the baking temperature ranges from 80 DEG C to 150 DEG C, and ion source parameters are set as follows: the cathode voltage ranges from 100 V to 300 V, and the ion beam current ranges from 1 A to 4 A; s02, before evaporation, carrying out ion bombardment on the lens chalcogenide glass for 3-10 minutes by the coating machine; s03, plating a first layer of Ge on the chalcogenide glass of the lens, and controlling the evaporation rate to be 0.2-0.8 nm / s; s04, plating a second layer of ZnS on the first layer of Ge, and controlling the evaporation rate to be 0.2-1.5 nm / s; s05, a third layer of YbF3 is plated on the second layer of ZnS, and the evaporation rate is controlled to be 0.2-1 nm / s; s06, plating a fourth layer of ZnS on the third layer of YbF3, and controlling the evaporation rate to be 0.2-1.5 nm / s; and S07, plating a fifth layer of Ge on the fourth layer of ZnS, wherein the evaporation rate is controlled to be 0.2-0.8 nm / s. The thin film provided by the invention effectively solves the problems of stress between film layers, film layer adhesive force and good spectral performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of infrared optical detection technology, and in particular to a process for preparing a cut-off film by evaporation on the surface of a chalcogenide glass. Background Art

[0002] At present, infrared detectors have been widely used in commercial applications, such as natural disasters, field search and rescue, remote sensing systems, infrared cameras, multi-spectral imaging instruments, etc. However, due to the interference of various factors such as the atmospheric environment, as the detection distance increases, the infrared information will be lost due to scattering or absorption, making the infrared information captured by the detector weaker; on the other hand, since the components used in infrared detectors have a large refractive index, the contact interface with the environment reflects the detected information, which greatly reduces the quantum efficiency of the detection device. Therefore, it is an important way to improve the comprehensive performance of the detection device to perform anti-reflection treatment on the corresponding band of the incident surface of the infrared detector and shield the interference of other bands on the detector. Summary of the invention

[0003] The purpose of the present invention is to provide a process for preparing a cut-off film by evaporating it on the surface of a chalcogenide glass, so as to solve the above-mentioned problem.

[0004] In order to achieve the above object, the present invention provides the following technical solution: a process for preparing a cut-off film by evaporating it on the surface of a chalcogenide glass, comprising the following steps:

[0005] S01, the initial vacuum degree of the coating machine before operation is better than 5.0×10 -4 Pa, the baking temperature is 80-150°C, and the ion source parameters are set as follows: cathode voltage 100-300V, ion beam current 1-4A;

[0006] S02, before evaporation, the coating machine bombards the lens chalcogenide glass with ions for 3-10 minutes;

[0007] S03, coating the first layer of Ge on the lens chalcogenide glass, and controlling the evaporation rate at 0.2-0.8nm / s;

[0008] S04, plate a second layer of ZnS on the first layer of Ge, and control the evaporation rate at 0.2-1.5nm / s;

[0009] S05, plate a third layer of YbF3 on the second layer of ZnS, and control the evaporation rate at 0.2-1nm / s;

[0010] S06, coating the fourth layer of ZnS on the third layer of YbF3, and controlling the evaporation rate at 0.2-1.5nm / s;

[0011] S07, coating the fifth layer of Ge on the fourth layer of ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0012] S08, coating the sixth layer of ZnS on the fifth layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0013] S09, coating the seventh layer of YbF3 on the sixth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s;

[0014] S10, coating the eighth layer of ZnS on the seventh layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0015] S11, coating the ninth layer of Ge on the eighth layer of ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0016] S12, coating the tenth layer of ZnS on the ninth layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0017] S13, coating the eleventh layer of YbF3 on the tenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s;

[0018] S14, coating a twelfth layer of ZnS on the eleventh layer of YbF3, and controlling the evaporation rate to be 0.2-1.5 nm / s;

[0019] S15, coating the thirteenth layer of Ge on the twelfth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8nm / s;

[0020] S16, coating the 14th layer of ZnS on the 13th layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0021] S17, coating the fifteenth layer of YbF3 on the fourteenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s;

[0022] S18, coating the sixteenth layer of ZnS on the fifteenth layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0023] S19, coating the seventeenth layer of Ge on the sixteenth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0024] S20, coating the eighteenth layer of ZnS on the seventeenth layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0025] S21, coating the nineteenth layer of YbF3 on the eighteenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s;

[0026] S22, coating the twentieth layer of ZnS on the nineteenth layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0027] S23, coating the 21st layer of Ge on the 20th layer of high ZnS, and controlling the evaporation rate at 0.2-0.8nm / s;

[0028] S24, coating the twenty-second layer of ZnS on the twenty-first layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0029] S25, coating the twenty-third layer of YbF3 on the twenty-second layer of ZnS, with the evaporation rate controlled at 0.2-1 nm / s;

[0030] S26, coating the twenty-fourth layer of ZnS on the twenty-third layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0031] S27, coating the twenty-fifth layer of Ge on the twenty-fourth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0032] S28, coating the twenty-sixth layer of ZnS on the twenty-fifth layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0033] S29, coating the twenty-seventh layer of YbF3 on the twenty-sixth layer of ZnS, with the evaporation rate controlled at 0.2-1 nm / s;

[0034] S30, coating the twenty-eighth layer of ZnS on the twenty-seventh layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0035] S31, coating the twenty-ninth layer of Ge on the twenty-eighth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0036] S32, coating the 30th layer of ZnS on the 29th layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0037] S33, coating the 31st layer of YbF3 on the 30th layer of ZnS, with the evaporation rate controlled at 0.2-1nm / s;

[0038] S34, coating a thirty-second layer of ZnS on the thirty-first layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0039] S35, coating the thirty-third layer of Ge on the thirty-second layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0040] S36, coating a thirty-fourth layer of ZnS on the thirty-third layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0041] S33, coating a thirty-fifth layer of YbF3 on the thirty-fourth layer of ZnS, with an evaporation rate controlled at 0.2-1 nm / s;

[0042] S34, coating a thirty-sixth layer of ZnS on the thirty-fifth layer of YbF3, with an evaporation rate controlled at 0.2-1.5 nm / s;

[0043] S35, coating a thirty-seventh layer of YbF3 on the thirty-sixth layer of ZnS, with an evaporation rate controlled at 0.2-1 nm / s;

[0044] S36. Plate a thirty-eighth layer of ZnS on the thirty-seventh layer of YbF3, and control the evaporation rate at 0.2-1.5 nm / s.

[0045] Preferably, the thirty-sixth layer of ZnS and the thirty-eighth layer of ZnS are evaporated using a barrier evaporation source.

[0046] Preferably, the first layer of Ge, the second layer of ZnS, the third layer of YbF3, the fourth layer of ZnS, the fifth layer of Ge, the sixth layer of ZnS, the seventh layer of YbF3, the eighth layer of ZnS, the ninth layer of Ge, the tenth layer of ZnS, the eleventh layer of YbF3, the twelfth layer of ZnS, the thirteenth layer of Ge, the fourteenth layer of ZnS, the fifteenth layer of YbF3, the sixteenth layer of ZnS, the seventeenth layer of Ge, the eighteenth layer of ZnS, the nineteenth layer of YbF3, the twentieth layer of ZnS, the twenty-first layer of Ge, the twenty-second layer of ZnS, the twenty-third layer of YbF3, the twenty-fourth layer of ZnS, the twenty-fifth layer of Ge, the twenty-sixth layer of ZnS, the twenty-seventh layer of YbF3, the twenty-eighth layer of ZnS, the twenty-ninth layer of Ge, the thirtieth layer of ZnS, the thirty-first layer of YbF3, the thirty-second layer of ZnS, the thirty-third layer of Ge, the thirty-fourth layer of ZnS, the thirty-fifth layer of YbF3 and the thirty-seventh layer of YbF3 are plated with an electron gun evaporation source.

[0047] Preferably, the first layer of Ge, the second layer of ZnS, the third layer of YbF3, the fourth layer of ZnS, the fifth layer of Ge, the sixth layer of ZnS, the seventh layer of YbF3, the eighth layer of ZnS, the ninth layer of Ge, the tenth layer of ZnS, the eleventh layer of YbF3, the twelfth layer of ZnS, the thirteenth layer of Ge, the fourteenth layer of ZnS, the fifteenth layer of YbF3, the sixteenth layer of ZnS, the seventeenth layer of Ge, the eighteenth layer of ZnS, the nineteenth layer of YbF3, the twentieth layer of ZnS, the twenty-first layer The physical thicknesses of the film layers in the 22nd layer Ge, the 23rd layer ZnS, the 24th layer ZnS, the 25th layer Ge, the 26th layer ZnS, the 27th layer YbF3, the 28th layer ZnS, the 29th layer Ge, the 30th layer ZnS, the 31st layer YbF3, the 32nd layer ZnS, the 33rd layer Ge, the 34th layer ZnS, the 35th layer YbF3, the 37th layer YbF3 and the 38th layer ZnS are as follows: 1 20±20nm、50±20nm、350±30nm、50±20nm、170±20nm、50±20nm、250±30nm、50±20nm、160±20nm、50±20nm、280±30nm、50±20nm、150±20nm、50±20nm、280±30nm、50±20nm、290±30nm、50±20nm、350±30nm、5 0±20nm, 270±30nm, 50±20nm, 450±30nm, 50±20nm, 260±30nm, 50±20nm, 660±40nm, 50±20nm, 330±30nm, 50±20nm, 610±40nm, 50±20nm, 250±30nm, 60±20nm, 200±20nm, 150±20nm, 900±40nm, 260±20nm.

[0048] Preferably, the ZnS is a zinc sulfide film.

[0049] Preferably, the Ge is a germanium film;

[0050] Preferably, the YbF3 is an ytterbium fluoride film.

[0051] In the above technical scheme, the present invention provides a process for preparing a cut-off film evaporated on the surface of a chalcogenide glass, which has the following beneficial effects: by evaporating a cut-off film on a chalcogenide glass substrate, the stress between film layers and the adhesion of film layers are effectively solved through reasonable film material selection and setting of optimal parameter conditions, and optical components of an infrared detection system with qualified spectral performance and qualified thin film reliability are obtained, so that the obtained film layer has both good spectral performance and good mechanical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0053] Figure 1 A schematic diagram of a membrane structure provided by an embodiment of the present invention;

[0054] Figure 2 A schematic diagram of the simulated transmittance (bold line) and reflectance structure provided by an embodiment of the present invention;

[0055] Figure 3 Infrared spectrogram provided by the embodiment of the present invention;

[0056] Figure 4 A Fourier transform diagram provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0057] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.

[0058] Embodiment 1

[0059] like Figure 1-2 As shown, a process for preparing a cut-off film by evaporating on the surface of a chalcogenide glass comprises the following steps:

[0060] S01, the initial vacuum degree of the coating machine before operation is better than 5.0×10 -4 Pa, the baking temperature is 80-150°C, and the ion source parameters are set as follows: cathode voltage 100-300V, ion beam current 1-4A;

[0061] S02, before evaporation, the coating machine bombards the lens chalcogenide glass with ions for 3-10 minutes;

[0062] S03, coating the first layer of Ge on the lens chalcogenide glass, and controlling the evaporation rate at 0.2-0.8nm / s;

[0063] S04, plate a second layer of ZnS on the first layer of Ge, and control the evaporation rate at 0.2-1.5nm / s;

[0064] S05, plate a third layer of YbF3 on the second layer of ZnS, and control the evaporation rate at 0.2-1nm / s;

[0065] S06, coating the fourth layer of ZnS on the third layer of YbF3, and controlling the evaporation rate at 0.2-1.5nm / s;

[0066] S07, coating the fifth layer of Ge on the fourth layer of ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0067] S08, coating the sixth layer of ZnS on the fifth layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0068] S09, coating the seventh layer of YbF3 on the sixth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s;

[0069] S10, coating the eighth layer of ZnS on the seventh layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0070] S11, coating the ninth layer of Ge on the eighth layer of ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0071] S12, coating the tenth layer of ZnS on the ninth layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0072] S13, coating the eleventh layer of YbF3 on the tenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s;

[0073] S14, coating a twelfth layer of ZnS on the eleventh layer of YbF3, and controlling the evaporation rate to be 0.2-1.5 nm / s;

[0074] S15, coating the thirteenth layer of Ge on the twelfth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8nm / s;

[0075] S16, coating the 14th layer of ZnS on the 13th layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0076] S17, coating the fifteenth layer of YbF3 on the fourteenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s;

[0077] S18, coating the sixteenth layer of ZnS on the fifteenth layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0078] S19, coating the seventeenth layer of Ge on the sixteenth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0079] S20, coating the eighteenth layer of ZnS on the seventeenth layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0080] S21, coating the nineteenth layer of YbF3 on the eighteenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s;

[0081] S22, coating the twentieth layer of ZnS on the nineteenth layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s;

[0082] S23, coating the 21st layer of Ge on the 20th layer of high ZnS, and controlling the evaporation rate at 0.2-0.8nm / s;

[0083] S24, coating the twenty-second layer of ZnS on the twenty-first layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0084] S25, coating the twenty-third layer of YbF3 on the twenty-second layer of ZnS, with the evaporation rate controlled at 0.2-1 nm / s;

[0085] S26, coating the twenty-fourth layer of ZnS on the twenty-third layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0086] S27, coating the twenty-fifth layer of Ge on the twenty-fourth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0087] S28, coating the twenty-sixth layer of ZnS on the twenty-fifth layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0088] S29, coating the twenty-seventh layer of YbF3 on the twenty-sixth layer of ZnS, with the evaporation rate controlled at 0.2-1 nm / s;

[0089] S30, coating the twenty-eighth layer of ZnS on the twenty-seventh layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0090] S31, coating the twenty-ninth layer of Ge on the twenty-eighth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0091] S32, coating the 30th layer of ZnS on the 29th layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0092] S33, coating the 31st layer of YbF3 on the 30th layer of ZnS, with the evaporation rate controlled at 0.2-1nm / s;

[0093] S34, coating a thirty-second layer of ZnS on the thirty-first layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0094] S35, coating the thirty-third layer of Ge on the thirty-second layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s;

[0095] S36, coating a thirty-fourth layer of ZnS on the thirty-third layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s;

[0096] S33, coating a thirty-fifth layer of YbF3 on the thirty-fourth layer of ZnS, with an evaporation rate controlled at 0.2-1 nm / s;

[0097] S34, coating a thirty-sixth layer of ZnS on the thirty-fifth layer of YbF3, with an evaporation rate controlled at 0.2-1.5 nm / s;

[0098] S35, coating a thirty-seventh layer of YbF3 on the thirty-sixth layer of ZnS, with an evaporation rate controlled at 0.2-1 nm / s;

[0099] S36. Plate a thirty-eighth layer of ZnS on the thirty-seventh layer of YbF3, and control the evaporation rate at 0.2-1.5 nm / s.

[0100] The thirty-sixth layer of ZnS and the thirty-eighth layer of ZnS are evaporated using a resist evaporation source.

[0101] In the above embodiment, the first layer of Ge, the second layer of ZnS, the third layer of YbF3, the fourth layer of ZnS, the fifth layer of Ge, the sixth layer of ZnS, the seventh layer of YbF3, the eighth layer of ZnS, the ninth layer of Ge, the tenth layer of ZnS, the eleventh layer of YbF3, the twelfth layer of ZnS, the thirteenth layer of Ge, the fourteenth layer of ZnS, the fifteenth layer of YbF3, the sixteenth layer of ZnS, the seventeenth layer of Ge, the eighteenth layer of ZnS, the nineteenth layer of YbF3, the twentieth layer of ZnS, the twenty-first layer of Ge, the twenty-second layer of ZnS, the twenty-third layer of YbF3, the twenty-fourth layer of ZnS, the twenty-fifth layer of Ge, the twenty-sixth layer of ZnS, the twenty-seventh layer of YbF3, the twenty-eighth layer of ZnS, the twenty-ninth layer of Ge, the thirtieth layer of ZnS, the thirty-first layer of YbF3, the thirty-second layer of ZnS, the thirty-third layer of Ge, the thirty-fourth layer of ZnS, the thirty-fifth layer of YbF3 and the thirty-seventh layer of YbF3 are plated using an electron gun evaporation source.

[0102] Further, in the embodiment, the first layer of Ge, the second layer of ZnS, the third layer of YbF3, the fourth layer of ZnS, the fifth layer of Ge, the sixth layer of ZnS, the seventh layer of YbF3, the eighth layer of ZnS, the ninth layer of Ge, the tenth layer of ZnS, the eleventh layer of YbF3, the twelfth layer of ZnS, the thirteenth layer of Ge, the fourteenth layer of ZnS, the fifteenth layer of YbF3, the sixteenth layer of ZnS, the seventeenth layer of Ge, the eighteenth layer of ZnS, the nineteenth layer of YbF3, the twentieth layer of ZnS, the twenty-first layer of The physical thickness of each film layer is as follows: the 22nd layer of Ge, the 23rd layer of ZnS, the 24th layer of ZnS, the 25th layer of Ge, the 26th layer of ZnS, the 27th layer of YbF3, the 28th layer of ZnS, the 29th layer of Ge, the 30th layer of ZnS, the 31st layer of YbF3, the 32nd layer of ZnS, the 33rd layer of Ge, the 34th layer of ZnS, the 35th layer of YbF3, the 36th layer of ZnS, the 37th layer of YbF3 and the 38th layer of ZnS The degrees are: 120±20nm, 50±20nm, 350±30nm, 50±20nm, 170±20nm, 50±20nm, 250±30nm, 50±20nm, 160±20nm, 50±20nm, 280±30nm, 50±20nm, 150±20nm, 50±20nm, 280±30nm, 50±20nm, 290±30nm, 50±20nm, 350±30nm m, 50±20nm, 270±30nm, 50±20nm, 450±30nm, 50±20nm, 260±30nm, 50±20nm, 660±40nm, 50±20nm, 330± 30nm, 50±20nm, 610±40nm, 50±20nm, 250±30nm, 60±20nm, 200±20nm, 150±20nm, 900±40nm, 260±20nm.

[0103] Furthermore, if the reference wavelength is set to 1000 nm, the refractive index thickness is the first layer of Ge, the second layer of ZnS, the third layer of YbF3, the fourth layer of ZnS, the fifth layer of Ge, the sixth layer of ZnS, the seventh layer of YbF3, the eighth layer of ZnS, the ninth layer of Ge, the tenth layer of ZnS, the eleventh layer of YbF3, the twelfth layer of ZnS, the thirteenth layer of Ge, the fourteenth layer of ZnS, the fifteenth layer of YbF3, the sixteenth layer of ZnS, the seventeenth layer of Ge, and the eighteenth layer of layer ZnS, the nineteenth layer YbF3, the twentieth layer ZnS, the twenty-first layer Ge, the twenty-second layer ZnS, the twenty-third layer YbF3, the twenty-fourth layer ZnS, the twenty-fifth layer Ge, the twenty-sixth layer ZnS, the twenty-seventh layer YbF3, the twenty-eighth layer ZnS, the twenty-ninth layer Ge, the thirtieth layer ZnS, the thirty-first layer YbF3, the thirty-second layer ZnS, the thirty-third layer Ge, the thirty-fourth layer ZnS, the thirty-fifth layer YbF3, The refractive thickness of each coating layer in the 36th layer of ZnS, the 37th layer of YbF3 and the 38th layer of ZnS is: 2.5-3.5, 0.4-0.8, 4-5, 0.4-0.8, 4-5, 0.4-0.8, 3-4, 0.4-0.8, 4-5, 0.4-0.8, 3.5-4.5, 0.4-0.8, 3.5-4.5, 0.4-0.8, 3.5-4.5, 0.4-0.8, 7.5-8 .5, 0.4-0.8, 4-5, 0.4-0.8, 6.5-7.5, 0.4-0.8, 5.5-6.5, 0.4-0.8, 6.5-7.5, 0.4-0.8, 8.5-9.5, 0.4-0.8, 8.5-9.5, 0.4-0.8, 8-8.5, 0.4-0.8, 6.5-7.5, 1-1.5, 2.5-3, 2.5-3, 12-13, 4.5-5.5.

[0104] It should be noted that in the above process, ZnS is zinc sulfide film, Ge is germanium film, and YbF3 is ytterbium fluoride film material.

[0105] Experimental Example 1

[0106] The film produced in Example 1 was tested for transmittance using a Thermo Fisher Fourier infrared spectrometer IS50. The obtained spectral curve met the requirements of the infrared detection system. Figure 3 and Figure 4 .

[0107] Combination Figure 3It can be seen that in the infrared spectrum test, as the infrared light power increases, the transmittance of the film is almost close to 0% at the power of 1000-5000nm; and as the infrared light power exceeds 5000nm, the transmittance component increases, and when the infrared light power exceeds 8000-12000nm, it remains flat, and when the infrared light power exceeds 13000nm, the transmittance is in a rapid decline.

[0108] Combination Figure 3 It can be seen that in the infrared spectrum test, the film is in the Fourier transform infrared spectrometer, which is used to analyze the infrared spectrum, providing a higher signal-to-noise ratio and more accurate wavelength measurement. When the infrared light power is within 7500-12500nm, the wavelength passing through the film is maintained at about 0.5%. When the infrared light power exceeds 12500nm, it is in a rapid rise structure, and when the infrared light power is below 7500nm, the wavelength passing through the film is maintained at more than 5%.

[0109] In summary, when the transmittance of the film provided by the present invention exceeds 8000-12000nm, the transmittance will remain in a constant state, and the transmittance is the maximum at this time. When it does not exceed 5000nm, the transmittance is almost zero, and when it is greater than 12500nm, the transmittance begins to decrease and is in a slow decrease, indicating that the film provided in the embodiment has good spectral performance.

[0110] Experimental Example 2

[0111] The membrane material produced in Example 1 is taken and environmental performance tests are performed, and adhesion test, immersion test, high and low temperature test, constant temperature and humidity test and salt spray test can be performed in sequence to simulate the performance changes of the membrane material under stress, immersion erosion, high temperature, normal temperature and humidity and salt spray environment. Since the above-mentioned experimental design materials are well known to technical personnel in this field, they will not be described in detail.

[0112] The specific experiments and experimental conclusions are as follows:

[0113] 1. Adhesion test: Use 1cm wide 3M tape to stick firmly on the surface of the film layer. After quickly pulling up the tape from the edge of the part toward the vertical direction of the surface, the film layer will not fall off or be damaged.

[0114] 2. Immersion test: The sample is completely immersed in distilled water or deionized water. After 96 hours, there is no abnormality in the film layer.

[0115] 3. High and low temperature test: Place the sample in a high and low temperature test chamber, keep the temperature at -40℃ for half an hour, quickly switch from -40℃ to 90℃ for half an hour, then quickly switch from 90℃ to -40℃ for half an hour, repeat 12 times, and there is no abnormality in the film layer.

[0116] 4. Constant temperature and humidity test: Place the sample in a constant temperature and humidity test box, set the temperature to 85°C and the humidity to 85% RH, and continue to verify for 12 hours. There is no abnormality in the film layer.

[0117] 5. Salt spray test: temperature 35±2℃, concentration of 4.9%~5.1% NaCl solution, spray continuously for 72 hours, no abnormality in the film layer.

[0118] In summary, by evaporating the cutoff film on the chalcogenide glass substrate and reasonably selecting the film material and setting the optimal parameter conditions, the stress between the film layers and the film adhesion are effectively solved, and the optical components of the infrared detection system with qualified spectral performance and qualified thin film reliability are obtained, so that the obtained film has both good spectral performance and good mechanical stability.

[0119] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A process for preparing a cut-off film by evaporating it on the surface of a chalcogenide glass, characterized in that: The following steps are involved: S01, the initial vacuum degree of the coating machine before operation is better than 5.0×10 -4 Pa, the baking temperature is 80-150°C, and the ion source parameters are set as follows: cathode voltage 100-300V, ion beam current 1-4A; S02, before evaporation, the coating machine bombards the lens chalcogenide glass with ions for 3-10 minutes; S03, coating the first layer of Ge on the lens chalcogenide glass, and controlling the evaporation rate at 0.2-0.8nm / s; S04, plate a second layer of ZnS on the first layer of Ge, and control the evaporation rate at 0.2-1.5nm / s; S05, plate a third layer of YbF3 on the second layer of ZnS, and control the evaporation rate at 0.2-1nm / s; S06, coating the fourth layer of ZnS on the third layer of YbF3, and controlling the evaporation rate at 0.2-1.5nm / s; S07, coating the fifth layer of Ge on the fourth layer of ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s; S08, coating the sixth layer of ZnS on the fifth layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s; S09, coating the seventh layer of YbF3 on the sixth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s; S10, coating the eighth layer of ZnS on the seventh layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s; S11, coating the ninth layer of Ge on the eighth layer of ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s; S12, coating the tenth layer of ZnS on the ninth layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s; S13, coating the eleventh layer of YbF3 on the tenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s; S14, coating a twelfth layer of ZnS on the eleventh layer of YbF3, and controlling the evaporation rate to be 0.2-1.5 nm / s; S15, coating the thirteenth layer of Ge on the twelfth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8nm / s; S16, coating the 14th layer of ZnS on the 13th layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s; S17, coating the fifteenth layer of YbF3 on the fourteenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s; S18, coating the sixteenth layer of ZnS on the fifteenth layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s; S19, coating the seventeenth layer of Ge on the sixteenth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s; S20, coating the eighteenth layer of ZnS on the seventeenth layer of Ge, and controlling the evaporation rate at 0.2-1.5 nm / s; S21, coating the nineteenth layer of YbF3 on the eighteenth layer of ZnS, and controlling the evaporation rate at 0.2-1 nm / s; S22, coating the twentieth layer of ZnS on the nineteenth layer of YbF3, and controlling the evaporation rate at 0.2-1.5 nm / s; S23, coating the 21st layer of Ge on the 20th layer of high ZnS, and controlling the evaporation rate at 0.2-0.8nm / s; S24, coating the twenty-second layer of ZnS on the twenty-first layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s; S25, coating the twenty-third layer of YbF3 on the twenty-second layer of ZnS, with the evaporation rate controlled at 0.2-1 nm / s; S26, coating the twenty-fourth layer of ZnS on the twenty-third layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s; S27, coating the twenty-fifth layer of Ge on the twenty-fourth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s; S28, coating the twenty-sixth layer of ZnS on the twenty-fifth layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s; S29, coating the twenty-seventh layer of YbF3 on the twenty-sixth layer of ZnS, with the evaporation rate controlled at 0.2-1 nm / s; S30, coating the twenty-eighth layer of ZnS on the twenty-seventh layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s; S31, coating the twenty-ninth layer of Ge on the twenty-eighth layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s; S32, coating the 30th layer of ZnS on the 29th layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s; S33, coating the 31st layer of YbF3 on the 30th layer of ZnS, with the evaporation rate controlled at 0.2-1nm / s; S34, coating a thirty-second layer of ZnS on the thirty-first layer of YbF3, with the evaporation rate controlled at 0.2-1.5 nm / s; S35, coating the thirty-third layer of Ge on the thirty-second layer of high ZnS, and controlling the evaporation rate at 0.2-0.8 nm / s; S36, coating a thirty-fourth layer of ZnS on the thirty-third layer of Ge, with the evaporation rate controlled at 0.2-1.5 nm / s; S33, coating a thirty-fifth layer of YbF3 on the thirty-fourth layer of ZnS, with an evaporation rate controlled at 0.2-1 nm / s; S34, coating a thirty-sixth layer of ZnS on the thirty-fifth layer of YbF3, with an evaporation rate controlled at 0.2-1.5 nm / s; S35, coating a thirty-seventh layer of YbF3 on the thirty-sixth layer of ZnS, with an evaporation rate controlled at 0.2-1 nm / s; S36. Plate a thirty-eighth layer of ZnS on the thirty-seventh layer of YbF3, and control the evaporation rate at 0.2-1.5 nm / s.

2. A process for preparing a cut-off film by evaporating on the surface of chalcogenide glass according to claim 1, characterized in that: The thirty-sixth layer of ZnS and the thirty-eighth layer of ZnS are evaporated using a resist evaporation source.

3. The process for preparing a cut-off film by evaporating on the surface of chalcogenide glass according to claim 1, characterized in that: When performing the first layer of Ge, the second layer of ZnS, the third layer of YbF3, the fourth layer of ZnS, the fifth layer of Ge, the sixth layer of ZnS, the seventh layer of YbF3, the eighth layer of ZnS, the ninth layer of Ge, the tenth layer of ZnS, the eleventh layer of YbF3, the twelfth layer of ZnS, the thirteenth layer of Ge, the fourteenth layer of ZnS, the fifteenth layer of YbF3, the sixteenth layer of ZnS, the seventeenth layer of Ge, the eighteenth layer of ZnS, the nineteenth layer of YbF3, the twentieth layer of ZnS, the twenty-first layer of Ge, the twenty-second layer of ZnS, the twenty-third layer of YbF3, the twenty-fourth layer of ZnS, the twenty-fifth layer of Ge, the twenty-sixth layer of ZnS, the twenty-seventh layer of YbF3, the twenty-eighth layer of ZnS, the twenty-ninth layer of Ge, the thirtieth layer of ZnS, the thirty-first layer of YbF3, the thirty-second layer of ZnS, the thirty-third layer of Ge, the thirty-fourth layer of ZnS, the thirty-fifth layer of YbF3 and the thirty-seventh layer of YbF3 are plated with an electron gun evaporation source.

4. The process for preparing a cut-off film by evaporating on the surface of chalcogenide glass according to claim 1, characterized in that: The first layer of Ge, the second layer of ZnS, the third layer of YbF3, the fourth layer of ZnS, the fifth layer of Ge, the sixth layer of ZnS, the seventh layer of YbF3, the eighth layer of ZnS, the ninth layer of Ge, the tenth layer of ZnS, the eleventh layer of YbF3, the twelfth layer of ZnS, the thirteenth layer of Ge, the fourteenth layer of ZnS, the fifteenth layer of YbF3, the sixteenth layer of ZnS, the seventeenth layer of Ge, the eighteenth layer of ZnS, the nineteenth layer of YbF3, the twentieth layer of ZnS, the twenty-first layer of Ge, the second The physical thicknesses of the film layers in the twelfth layer of ZnS, the twenty-third layer of YbF3, the twenty-fourth layer of ZnS, the twenty-fifth layer of Ge, the twenty-sixth layer of ZnS, the twenty-seventh layer of YbF3, the twenty-eighth layer of ZnS, the twenty-ninth layer of Ge, the thirtieth layer of ZnS, the thirty-first layer of YbF3, the thirty-second layer of ZnS, the thirty-third layer of Ge, the thirty-fourth layer of ZnS, the thirty-fifth layer of YbF3, the thirty-sixth layer of ZnS, the thirty-seventh layer of YbF3 and the thirty-eighth layer of ZnS are respectively :120±20nm, 50±20nm, 350±30nm, 50±20nm, 170±20nm, 50±20nm, 250±30nm, 50±20nm, 160±20nm, 50±20nm, 280±30nm, 50±20nm, 150±20nm, 50±20nm, 280±30nm, 50±20nm, 290±30nm, 50±20nm, 350±30nm, 50±20nm, 270±30nm, 50±20nm, 450±30nm, 50±20nm, 260±30nm, 50±20nm, 660±40nm, 50±20nm, 330±30nm, 50±20nm, 610±40nm, 50±20nm, 250±30nm, 60±20nm, 200±20nm, 150±20nm, 900±40nm, 260±20nm.

5. The process for preparing a cut-off film by evaporating on the surface of chalcogenide glass according to claim 1, characterized in that: The ZnS is a zinc sulfide film.

6. The process for preparing a cut-off film by evaporating on the surface of chalcogenide glass according to claim 1, characterized in that: The Ge is a germanium film.

7. The process for preparing a cut-off film by evaporating on the surface of chalcogenide glass according to claim 1, characterized in that: The YbF3 is an ytterbium fluoride film.